Kekerasan Terhadap Perempuan (Tinjauan Sosiologi) - Ayun Ayun (P-2623-0291)
Theoretically, the concept of sociology does not focus on issues that have relevance to violence against women. The main study of sociology actually refers more to phenomena and aspects of the social life of the community, with all components and elements that are affiliated in it. If the context of violence is captured by using sociological approaches and studies, the direction of the discussion and discussion will certainly focus on several problems that include; (1) Review of violence against women as a product of social life. (2) Violence against women as a social deviation of life. (3) Violence against women as an indicator of dysfunction in the social system. With restrictions on the study of these three problems, exploration and analysis of violence that occurs in people's lives, especially against victims, namely women will be focused on deepening the sociological aspects, particularly the dynamics of social life. This is an anti-alternative which seems to make it possible for the disclosure of violence against women to be preached by being tested and able to answer questions; Why and with what factors so that violence against women occurs and even tends to experience an increase in unit size and frequency of events with the number of calculations of people who become victims. The social phenomenon that occurs in adulthood now shows invisible about bad events and tends to harm women. Violent acts or actions that lead to insults, harassment, abuse, beatings, isolation, threats and even trafacing (trafficking in women), exploitation and others related to physical, sexual, and psychological harm and suffering to victims as if they were only directed at women . With such reality, it appears that the life of the social community is in a dysfunctional condition. The extent to which community development and development plans are carried out are able to reconstruct a conducive social life so that acts of violence / criminalization can be eliminated